Effects of salt stress on expression level of StDREB2 transcription factor and microtuberization of different potato genotypes - N. K. Şahin; B. Benlioğlu; H. A. A. Ahmed; S. Uranbey1 (Journal of Animal and Plant Sciences, 2026)
Salt stress considerably limits plant development and growth and it has detrimental effects on crop production. Potato is also one of the moderately sensitive crops to salinity and it is very important to improve new potato varieties conferring salt tolerance. In vitro micro tubers are valuable materials for evaluation and in vitro selection of potato germplasm. The main aim of this study was to reveal the effects of different salt concentrations (100, 200 and 300 mM) on microtuberization of four potato cultivars i.e., Slaney, Granola, Rasin Busset and Agria. In addition to detect expression levels of dehydration-responsive element binding 2 (StDREB2) transcription factor involving in the transcriptional regulation of gene expression to various salt stresses in potato. On average, in all the potato cultivars the production of microtubers was drastically affected and decreased with increased salt intensity. The highest explant ratio forming micro tuber (66.6 %) and the highest number of micro-tubers (0.88) micro tubers / explant) were observed in cultivar Slaney. However, Granola could not produce any microtuber under salt stress conditions. The RT-qPCR regarding StDREB2 relative gene expression levels showed noticeable differences among potato genotypes for various NaCl concentrations. StDREB2 gene relative gene expression level was also up regulated at 100 mM and higher salt concentrations for almost all the cultivars except cv. Granola.
Keywords: Potato; salt; microtuberization; transcription factor; DREB; StDREB2